Optimal dimensions and performance evaluation of a truncated spherical dielectric lens antenna at X-band frequencies - Syed Zeeshan Ali; Kamran Ahsan; Danish ul Khairi; Syed Akhter Raza; Wadee Alhalabi; Lina Hussain Kazem; Muhammad Shahid Anwar (PLoS ONE, 2025)
This study presents the design and development of a truncated spherical dielectric lens antenna. The primary goal of this research is to significantly improve and optimize the directivity and beamwidth characteristics of the feed antenna by adjusting the feed position around the focal point of the lens. Polytetrafluoroethylene (PTFE), with a dielectric constant of 2.1, is chosen as the lens medium. Simulations are carried out using the CST-Studio Suite across the span of 8 to 12 GHz. Vector Network Analyzer (VNA) and an anechoic chamber are utilized for experimental validation. Directivity of 21.9 dBi and a beamwidth of 13.1° have been achieved by optimizing the dimensions of 24.34 mm thickness, 55 mm center of curvature and 110 mm aperture of the lens. By utilizing its simple geometrical shape, compact size, and ease of design and construction, this dielectric lens antenna is ideal for RF applications, particularly when energy concentration is necessary.